Response Growth And Production Plant Mustard Bitter ( Brassica juncea L.) Regarding Time Intervals and Dosages Giving Fertilizer Organic Liquid Azolla With System Drip Irrigation - Efendi, Bagus; Hasbi, Hudaini; Wijaya, Insan; Jalil, Abdul (Universitas Muhammadiyah Jember, 2024)
Availability content material organic its low ground and time application proper fertilizer _ is a factor inhibitor For increase growth and production plant mustard bitter . POC Azolla has very high N content because Azolla is symbiotic with N 2 fixing cyanobacteria into ammonia ie Annabaena Azollae. Study This aim For know influence of time interval Azolla POC administration , dosage administration of Azolla POC, and interactions between time intervals and doses administration of Azolla POC to growth and production plant mustard bitter ( Brassica juncea L.). Study This held month , December 2021 - March 2022 in Lahan Test Faculty Agriculture, Muhammadiyah University of Jember . Study This use Randomized Block Design (RCBD) Factorial consisting of from two factor . Two factor the namely the time interval administering POC Azolla (I) in 3 levels , namely : I1 = 4 days once , I2 = 5 days once , I3 = 6 days once and dose giving POC Azolla (P) in 4 levels , namely P0 = 0ml/m2 , P1 = 100 ml/m2 , P2 = 200 ml/m2 , P3 = 300 ml/m2 , each repeated 3 times. Research result show treatment interval time and dose giving POC Azolla has an effect to growth and production plant mustard bitter , and present interaction between treatment interval time and dose administration of Azolla POC.